Comet in Moominland - Jansson, Tove (Jansson, Tove. Moomin books, 2010)
When Moomintroll learns that a comet will be passing by, he and his friend Sniff travel to the Observatory on the Lonely Mountains to consult the Professors. Along the way, they have many adventures, but the greatest adventure of all awaits them when they learn that the comet is headed straight for their beloved Moominvalley.